Retirement or no Retirement? The Decision’s Effects on Cognitive Functioning, Well-Being, and Quality of Life - Carmen María Sarabia-Cobo; Victoria Pérez; Carmen Hermosilla; Pablo de Lorena (Behavioral Sciences, 2020)
This study addressed the psychological effects on personal well-being and reported quality of life of staying professionally active in late adulthood, and to what extent years of professional inactivity modulates cognitive abilities. Design and Methods: We collected data on 262 elderly adults, 129 of whom were professionally active elderly adults (who voluntarily maintained their professional activity after the age of retirement) and 133 of whom were retired adults, in a set of experimental tasks to measure basic cognitive resources. The study took place during the first quarter of 2020. Results: Active elderly people performed better on cognitive tasks that assessed attention, memory, and solving abilities and also reported more satisfaction with life and their current work. Multiple linear regressions analyses revealed that years of inactivity were associated with lower cognitive performance. Mentally demanding jobs were significantly associated with memory performance, but not with attention and planning. Conclusions: An involuntary separation from professional activity in the beginning of late adulthood may cause a deeper decline of cognitive functions, poorer adaptive adjustment to the aging process, and higher dissatisfaction with the period of life the individual is going through.